1997
DOI: 10.1097/00005537-199709000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Unilateral Vestibular Schwannoma

Abstract: Vestibular schwannoma (VS) may present clinically in one of two forms: sporadic unilateral or hereditary bilateral. Almost all cases of familial transmission have been associated with the diagnosis of neurofibromatosis type II (NF-2). In this report, we describe nine families (18 individuals) presenting with unilateral VS without evidence of NF-2. In four of the nine families, the affected individuals were of parent-offspring relationship, in three families they were cousin-cousin, and in the remaining two fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…VS may present clinically in one of two forms: sporadic unilateral or hereditary bilateral [10]. An increasing incidence was reported from Denmark for the time period 1977-1995 [11].…”
mentioning
confidence: 99%
“…VS may present clinically in one of two forms: sporadic unilateral or hereditary bilateral [10]. An increasing incidence was reported from Denmark for the time period 1977-1995 [11].…”
mentioning
confidence: 99%
“…Rarely, schwannomatosis caused by pathogenic variants in the LZTR1 gene can cause isolated VS, or VS that can be misdiagnosed as NF2. A previous report in this journal over 20 years ago suggested that familial occurrence of unilateral VS occurred more frequently than by chance, and this might be due to germline variants in the NF2 gene . We are not aware of any reports since to validate this theory.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, to demonstrate the sensitivity of testing, both mutational events were present in nine tumors that were tested, completely ruling out an inherited variant, as these were not present in the germline. Familial occurrence has been previously suggested to occur more often than by chance . The previous report of nine families—four with first‐degree relatives affected—did not undertake molecular testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations